2021
DOI: 10.1021/acs.chemrestox.0c00501
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Protective Response Associated with Expressional Alterations in Neuronal G Protein-Coupled Receptors in Polystyrene Nanoparticle Exposed Caenorhabditis elegans

Abstract: In this study, the association of expressional alterations in neuronal G proteincoupled receptors (GPCRs) with induction of protective response to polystyrene nanoparticles (PS-NPs) was investigated in Caenorhabditis elegans. On the basis of both phenotypic analysis and expression levels, the alterations in expressions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 68 publications
(124 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, many stress conditions that involve intestinal FSHR-1 are linked to oxidative stress responses ( e.g. , production of reactive oxygen species, ROS) ( Miller et al, 2015 ; Powell et al, 2009 ; Wang et al, 2023 , Yang et al, 2021a ). Under normal and oxidative stress conditions, fshr-1 mutants also exhibit reduced frequency of body bending in liquid medium, a motility-based readout of neural signaling activity at neuromuscular junctions ( Wei and Kowalski, 2018 ).…”
Section: Evolutionary Conservation Of Glycoprotein Hormone-like Signa...mentioning
confidence: 99%
“…Interestingly, many stress conditions that involve intestinal FSHR-1 are linked to oxidative stress responses ( e.g. , production of reactive oxygen species, ROS) ( Miller et al, 2015 ; Powell et al, 2009 ; Wang et al, 2023 , Yang et al, 2021a ). Under normal and oxidative stress conditions, fshr-1 mutants also exhibit reduced frequency of body bending in liquid medium, a motility-based readout of neural signaling activity at neuromuscular junctions ( Wei and Kowalski, 2018 ).…”
Section: Evolutionary Conservation Of Glycoprotein Hormone-like Signa...mentioning
confidence: 99%
“…Decreased insulin signaling leads to altered expression of DAF-16 target genes involved in detoxification response ( Freedman et al, 1993 ; Honda and Honda, 1999 ). Other studies showed the activation on ERK/MAPK or p38/MAPK in the neurons ( Yang et al, 2021 ) and changes to the JNK/MAPK and the insulin signaling in the intestinal cells of C. elegans upon PS-NP exposure ( Qu et al, 2020b ; Liu et al, 2021d ). These pathways are all hallmarks of oxidative stress response.…”
Section: Signaling Pathways Involved In Mp/np-induced Reproductive To...mentioning
confidence: 99%
“…For example, using meta-analysis, Oh et al extracted 1741 data samples of cadmium-containing semiconductor quantum dots and cellular toxicity from published literature . Much data on the interactions between model animals (such as Caenorhabditis elegans, Daphnia magna, zebrafish, rats, and mice) and NMs are available. Using meta-analysis to establish databases and then ML algorithms to study the interactions between model animals and NMs has great advantages. For example, ML has been used for the high-throughput screening phenotyping of Caenorhabditis elegans embryos .…”
Section: Investigation Of the Interactions Between Nms And Biologymentioning
confidence: 99%